Effect of pretreatment on production of citric acid from oil palm empty fruit bunches as substrate by wild aspergillus niger - Bari, Md. Niamul; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah; Samiur Rashid, Md. Shah (2008)
An investigation was carried out to evaluate the effect of pretreatment of oil palm empty fruit bunches (EFB) as new substrate for the production of citric acid through solid state bioconversion (SSB) in laboratory scale by Aspergillus niger. The experiment was carried out to observe the productivity of citric acid with treated and non-treated EFB in 250 ml Erlenmeyer flasks. The result obtained through this study showed that the production of citric acid increased due to the pretreatment in longer bioconversion time. The maximum production of citric acid of 183.702.5 g/kg of dry EFB with the production rate of 18 g/kg-day was obtained from EFB treated by boiling in water after 10 days of bioconversion. However, the production of citric acid of 1210.7 g/kg of dry EFB with the production rate of 20.2 g/kg-day was higher until 6 days of bioconversion from non-treated EFB that could be economically feasible, technically viable considering the pretreatment cost and shorter production duration